Treatment of Recurrent Bacterial Cystitis by Intravesical Instillations of Hyaluronic Acid - Zabkowski, Tomasz; Jurkiewicz, Beata; Saracyn, Marek (Urology Journal, 2015)
Purpose: To evaluate the results of intravesical instillations of hyaluronic acid (HA) in the treatment of recurrent bacterial cystitis (RBC), and to assess the rate of tolerability, the rate of recurrence of RBC and side effects of treatment. Materials and Methods: The study included 23 female patients from September 2012 to May 2013, aged 28-42 years. Twenty three women with a history of RBC, received intravesical instillations of HA once weekly for 6 weeks then once monthly for 8 months. Results: In 16 (69.6%) of patients, symptoms of RBC resolved after 8 months. In 5 (21.7%) patients after 8 months of HA treatment, urgency was reduced only by 30%. Therefore, it was decided to use combined therapy of HA and alpha blockers in this cohort group. There was a specific reduction (75%) in frequent urination at day and at night without urgency. Despite the use of above mentioned treatment, in 2 (8.7%) patients, RBC was still present and therefore the treatment was discontinued. Conclusion: The use of HA protects mucosa of urinary bladder and alleviates symptoms of infection. The intravesical instillations of HA and combination of HA + alpha blockers seems to be an effective therapeutic alternative in patients with RBC.